Suberin Production by Isolated Tomato Fruit Protoplasts - Rao, Gonella S. R. L. (1984)
The multilamellar wall secreted by protoplasts isolated from locule tissue of tomato (Lycopersicon esculentum L.) fruit was purified, and an extract was obtained after depolymerization with BF(3)-methanol. Analysis of this extract using thin layer chromatography demonstrated the presence of fatty acid methyl esters, fatty alcohols, dicarboxylic acid dimethyl esters, and ω-hydroxy acid methyl esters. These components were quantified using an Iatroscan thin layer chromatography-flame ionization detection system. The different chain lengths in each group were identified and quantified using gas chromatography. The results clearly indicated the presence of suberin.